Green approaches in the synthesis of furan-based diepoxy monomers - Marotta, Angela; Ambrogi, Veronica; Cerruti, Pierfrancesco; Mija, Alice (RSC advances, 2018)
Two eco-respectful, one-step synthetic routes for the preparation of a bio-based epoxy monomer derived from furan precursors are developed. The diglycidyl ester products are throughly characterized in terms of structure and thermal properties. Gathered results indicate that the two selected approaches allow the preparation of pure, furanic diglycidyl ester, which represents a viable bio-based alternative to its petrochemical aromatic counterpart.